Avaliação da atividade fotoeletrocatalitica de eletrodo baseado em Ti/RuO2-TiO2 modificado com óxidos de Estanho e Tântalo para a degradação do corante Azul Índigo - Tomaz, Alveriana Tagarro (2023)
Indigo Blue (IB) is a dye widely used by the textile sector for dyeing cellulosic fibers of cotton and jeans, being considered a recalcitrant substance, therefore resistant to traditional treatments. Several methodologies are reported in the literature for the removal or degradation of dyes from the aqueous medium, among these methodologies the advanced oxidative processes (AOPs) stand out, which use the in situ formation of highly reactive oxidant species in the degradation of the pollutant. Photoelectrocatalysis is an AOP that employs photocatalysis combined with electrocatalysis and shows promising results in the degradation of dyes when using a dimensionally stable anode (DSA) as the photoanode. In the present study, we sought to investigate the efficiency of an DSA prepared by the thermal decomposition method of polymeric precursors based on Ti/RuO2-TiO2 modified with tin and tantalum oxides. These ADEs were analyzed by physical (X-ray diffraction, scanning electron microscopy and energy dispersive X-ray) and electrochemical (cyclic voltammetry) techniques. Then, IB dye (100 mg L-1 ) degradation assays were performed using NaCl as support electrolyte, by photocatalysis, electrocatalysis and photoelectrocatalysis techniques. The compositions Ti/RuO2-TiO2-SnO2Ta2O5 (30:40:10:20), Ti/RuO2-TiO2- SnO2 (30:60:10), Ti/RuO2-TiO2-Ta2O5 (30:50:20) and Ti/RuO2-TiO2 (30:70) were tested, so that the ternary compositions stood out. By using the photoelectrocatalysis technique, it was possible to obtain a removal of 100% in 40 min with a current of 20 mA. The influence of the color removal current was also analyzed, so that, when using a current of 100 mA, a 100% color removal was obtained in 20 min. The electrolyte concentration was also studied, since NaCl acts by generating chlorinated species that will degrade AI, thus, the lower the NaCl concentration, the slower the process. Finally, the chemical oxygen demand (COD) of the medium during the photoelectrocatalysis process was also analyzed, with a COD removal of 55%.